Pengaruh Minat Belajar Terhadap Hasil Belajar Mata Pelajaran IPS Siswa Kelas VIII Di SMP Negeri 05 Seluma - Soeharto Soeharto; Rossa Ayuni (Universitas Dehasen Bengkulu, 2023)
This study aims to determine the interest in learning social studies subjects at SMP Negeri 05 Seluma, to determine the learning outcomes of social studies subjects at class VIII students at SMP Negeri 05 Seluma, and to determine the effect of interest in learning on learning outcomes in social studies subjects for class VIII students, at SMP Negero 05 Seluma. This research uses descriptive quantitative approach. The population in this study were all students of SMP 05 Seluma, totaling 445 students for the 2021/2022 academic year. The sampel in this study is class VIII 2 students, totaling 24 students. The techniquue of collecting research data is based on observations and questionnaires. The research data analysis technique uses the average analysis, then by calculating the percentage, simple linear regression analysis, testing linearity using anova tables, checking regression linearity, and correlation coefficients (influence). From the results of the research and discussion in this study, regarding the relationship between students’ learning interest in social studies subjects for class VIII SMPN 05 Seluma, it can be concluded that there is “The Influence of Learning Interests on Learning Outcomes of Social Studies Subjects for Class VIII Students at SMP Negeri 05 Seluma.